Hiperdiscurso de divulgação científica midiática: investigando hiperligações em notícias digitais nas revistas Galileu e Superinteressante - Glück, Eduardo Paré (Universidade do Vale do Rio dos Sinos, 2019)
This dissertation, in the scope of the hyperdiscourse in digital science news, aims to investigate how the hyperlinks presented in a corpus of digital news of science dissemination manifest themselves discursively. Specifically, it is intended to clarify the hypertextual discursivity and the meanings produced by the discursive mechanism in focus in this dissertation, the hyperlink. This study comprises description, analysis and interpretation of a corpus composed of ten digital news of scientific dissemination, from Galileu and Superinteressante magazines, to answer the following research questions: how do the hyperlinks present in a digital news corpus of science dissemination manifest themselves discursively – their technodiscursive configuration and rhetorical effect? What is the relevance of the link to scientific dissemination? This is a quantitative or a qualitative study, or mixed, according to Creswell (2010). This research is supported by the following theorists and their respective contributions: (a) Charaudeau (2007; 2009; 2016), with his studies on the discourse of mediatization of science; (b) Marchuschi (2001), Santaella (2014), Koch (2007), Canavilhas (2014) and Coscarelli (2012), with their investigations on hypertext and hypertextuality; (c) Paveau (2013a; 2013b; 2015; 2016; 2017a; 2017b), with the notions of technodiscourse; (d) Mann and Thompson (1989), Bernárdez (1995) and Giering (2007), with aspects related to Rethorical Structure Theory (RST). It is concluded that intradiscursive hyperlinks manifest themselves as technowords or technosegments, depending on the choice of the textual producer of the news. As for its rhetorical effect, the relations that emerged predominantly were Fund and Evidence, which aim to increase the writer's capacity for what was informed at the core or to give credibility to the subject matter, respectively. It is assumed that the presence of hyperlinks serves the purpose postulated by Charaudeau (2009) – to inform and to capture -, since it is through them that the readwriter has access to other scientific documents or popularization of science. Finally, it is emphasized that this study can offer a broader view of the technodiscourse in digital news of scientific dissemination, as well as a contribution to studies in Applied Linguistics.
Keywords: Hiperdiscurso; Hiperligação; Notícia Digital; Divulgação científica; Galileu; Superinteressante; Hyperdiscourse; Hyperlink; Digital News; Scientific Dissemination; Galileu; Superinteressante; ACCNPQ::Lingüística, Letras e Artes::Lingüística